Taper junctions in modular hip joint replacements: what affects their stability? - Müller, Ulrike; Bormann, Therese; Schröder, Stefan; Kretzer, Jan Philippe (Journal of the mechanical behavior of biomedical materials, 2021)
Background - Although taper junctions are beneficial in the reconstruction of hip joints, some clinical concerns like the formation of adverse local tissue reactions have recently emerged. These reactions are associated with wear and corrosion products from the interface of insufficient taper connections regarding strength. Commonly used tapers vary in their geometric and topographical design parameter. Therefore, this study aims to evaluate interactions between design and surgical related parameters to the taper connection strength. - Methods - In this study, the effect of the taper contact situation, surface roughness and head material in combination with assembly force on the taper connection strength were assessed using torque-off tests. Furthermore, the type of use in terms of single-use or re-use of the stem taper was investigated. - Results - The study showed that the impaction force is the predominant factor that determines the taper strength followed by the type of use and the head material. The contact situation seems to slightly influence the determined torque-off moment, whereas the surface topography of the stem taper obviously plays a minor role for the taper connection strength. - Conclusion - Clinical users should be aware that an increased assembly force will strengthen the stability of the taper junction, whereas care should be taken when reusing hip stems with metal heads as this may decrease their connection strength.
Gesehen am 06.08.2021